Prevalência e fatores determinantes de sobrepeso e obesidade em mulheres da região semiárida do Brasil - Olímpio, Pedro Henrique Gomes (2021)
Developed and developing countries commonly have registered a large increase in the prevalence rates of overweight and obesity, classifying this situation as a serious problem for public health. This problem can be caused or aggravated by multiple factors, resulting from the relationship between genetic, metabolic, social, behavioral and cultural factors. The study analyzed the prevalence and determinants of overweight and obesity in women of reproductive age in the semiarid region of Brazil. In the cluster sample of 3200 households in the state of Ceará, women between 15 and 49 years of age were surveyed. Nutritional status was measured by the Body Mass Index. To investigate possible associations between the variables of interest, regression models with logit link adjusted for complex samples were used. 25.2% had a body mass index (BMI) compatible with obesity and 35.0% with overweight. Altogether, 60.2% of these women lived with excessive levels of weight, among them, the highest prevalence was found in the age groups of 20 and 30 years of age. In the adjusted analysis, obesity was positively associated with: When adjusted for each other, overweight was positively associated with: age >40 years (PR=1.37), age at menarche <12 years (PR=1.17), having had three or more children (PR=1.17). Health-related factors were hypertension (PR=1.15) and body image dissatisfaction (PR=4.24). Overweight and obesity are highly prevalent in the semiarid region of Brazil. The reproductive factors identified point to the need to mobilize prenatal, postpartum and family planning services to prevent and control obesity. Certainly, significant benefits related to physical and mental health can be achieved with the reduction of overweight and obesity rates, such as the control of chronic diseases and a high sense of self-esteem in the population. The results found in this study can serve as a guide to contribute to the planning and implementation of policies and programs aimed at long-term prevention actions and, at the same time, aimed at women at different stages of the life cycle.